KARAKTERISASI ISOLAT Pestalotiopsis sp. DARI BEBERAPA INANG DAN PATOGENISITASNYA PADA TANAMAN KARET (Hevea brasiliensis) - Yusnizar, Mella; Bahri, Syamsul; Marnita, Yenni; Kusdiana, Alchemi Putri Juliantika (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
The diversity of Pestalotiopsis sp. hosts raises questions about whether Pestalotiopsis sp. originating from various hosts have the same characteristics as Pestalotiopsis sp. originating from rubber plants and their potential as pathogens in rubber plants. This study was conducted to identify the morphological characteristics of Pestalotiopsis sp. from various hosts and assess the potential for its pathogenic ability from various hosts in rubber plants. The study was conducted at the Sungei Putih Research Unit, Rubber Research Center, Galang District, Deli Serdang Regency, North Sumatra. The study was conducted from February to June 2023. This study consisted of two main activities: characterization of Pestalotiopsis sp. isolates and laboratory testing of the pathogenicity of these isolates on rubber plants. The study used a non-factorial completely randomized design (CRD). The characteristics of the Pestalotiopsis sp. colony diameter continued to increase. Colonies with almost identical characteristics are white, have a smooth texture, resemble a flower pattern formed on their mycelium, and have conidiomata that are shaped like small black dots in the middle and are irregularly distributed. Microscopic identification of Pestalotiopsis sp. fungi. from various hosts showed similar characteristics, including having five cells, fusiform and oval conidia with four brown septa, and two hyaline centulae with basal pedicels. Pathogenicity testing of Pestalotiopsis sp. isolates from various hosts showed that the rubber plant host had the highest lesion diameter compared to other hosts.